Allocation of rights to tax active business income - an analysis from the perspective of Brazil, India and China - Sharma, D (2016)
This thesis analyses whether the existing international framework for allocation of rights to tax active business income can be considered fair or equitable from the perspective of Brazil, India, and China (the BICs) and suggests steps that could be taken in the short and medium terms to advance fairness. Chapter I highlights the challenges in the framework from the standpoint of the BICs and also other developing countries. It is argued that an understanding of these concerns is important to achieve the OECD’s Base Erosion and Profit Shifting project’s aim of a certain and stable arrangement. Chapter II contends that fairness in both the rule-making process and the rules is critical to this end. Chapters III-V examine the evolution and development of the prevailing rules for division of rights to tax active business income and the key aspects of these rules from the BICs’ perspective based on the parameters for assessing procedural and substantive fairness established in chapter II. It is discussed that the BICs either had no or ineffective participation in the formulation of these rules. Resultantly, the BICs diverge from some of the basics of the rules towards positions that better account for these countries’ contributions in the generation of global profits. Chapter VI proposes enhancing the authority and legitimacy of the UN’s Committee of Experts on International Cooperation in Tax Matters as both a short and medium term option for fairer international taxation rule-making for the BICs, and, importantly, other developing countries as well. Chapter VII suggests a significant economic presence test for nexus along with a low rate withholding tax, and the greater use of the profit split method as steps towards a fairer allocation of taxing rights from the perspective of the BICs. Further analysis of theoretically superior but longer-term alternatives, such as global formulary apportionment, is also recommended.